Determination of Reactivity Ratios of N-butyl Acrylate/methyl Methacrylate Copolymerization by NMR Spectroscopy - Pham, Trung Quang; Bui, Yen Linh Tran; Hoang, Nhat Trinh; Do, Dang Van; Nguyen, Ngoc Minh (VNU Journal of Science: Natural Sciences and Technology, 2024)
In this study, the reactivity ratios of n-butyl acrylate (BA) and methyl methacrylate (MMA) were investigated. The copolymerization reactions were performed in toluene at 70 oC, using azobisisobutyronitrile as the initiator. The composition of the initial monomer mixture and copolymers was easily determined with the help of proton nuclear magnetic resonance (1H-NMR) spectroscopy. The molar fractions of BA and MMA in the feed were varied to apply the linear methods of Fineman–Ross and Kelen - Tudos. The calculation gave the reactivity ratios   and  . The computed copolymer composition was relatively close to the real copolymers obtained, with a 5% deviation.